A case of endogenous endophthalmitis after a mild dental infection - Hunter Hoopes; Nicole Cloutier (Journal of the American College of Emergency Physicians Open)
Abstract Endophthalmitis is a rare but severe vision threatening disease that most often occurs in patients with a recent history of ophthalmic surgery or penetrating trauma to the eye. Often these patients have underlying risk factors or are immunosuppressed. We present a case of endogenous endophthalmitis in an otherwise healthy male after a tooth extraction. This case highlights the importance of early recognition of emergent eye conditions and “red flags” with a thorough history and physical examination.